Psychological Distress and Coping among Caregivers of Patient with Mental Disorder: A hospital based cross sectional study - Khanal, Pratibha; Khatiwada, Manisha (Journal of Karnali Academy of Health Sciences, 2021)
Background: Caregivers of mentally ill patient are at risk of being subjected to psychological distress as they routinely provide assistance and supervision to their mentally ill relatives. Caring mentally ill relatives is a huge responsibility which demands a lot of time. Ill relatives require not only physical help but also emotional support. The study aimed to find out the psychological distress and coping strategies among caregivers of patient with mental illness.Methods: A descriptive cross-sectional study was conducted at department of Psychiatry Kathmandu Medical College, Nepal from December 30, 2019 to April 30, 2020. One hundred and eighty-five participants were chosen purposively. Face to face interview was conducted using standard tools (Kessler Psychological Distress Scale and Brief Cope Scale).Results: Among 185 caregivers 81.6% showed no sign of psychological distress whereas 18.4% showed mild to severe psychological distress. Caregivers used approach coping strategies 32.7±5.48 over avoidance coping strategies 19.88±3.79. There is moderately positive correlation (r=0.45) between psychological distress and avoidance coping strategies and this correlation is statistically significant (p=0.01). As the psychological distress increases caregivers used avoidance coping mechanism.Conclusion: Caregivers faced mild to severe psychological distress while providing care to mentally ill relatives thus use of various coping strategies like informational support, active coping, religion helped to reduce the distress.